Improve Learning Outcomes of Basketball Lay Up Shoot in Junior High School - Taufik, Muhamad Syamsul; Solahuddin, Soleh; Arisman, Arisman; Ridlo, Azi Faiz; Iskandar, Tatang (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
This research is motivated by the fact about the lack of student grades in the practice of lay up in basketball lessons. The purpose of this research is to be able to improve the learning outcomes of basketball lay up basketball in class VII-8 students at SMP Negeri 1 Ciawi through the section method. The method used is a classroom action research method. The research subjects were students of class VII-8 Ciawi Public Middle School, which consisted of 14 male students and 18 female students, with a total of 32 students. The results of the research analysis showed that there was an increase in basketball lay-up technique skills in the VII-8 grade students of SMP Negeri 1 Ciawi through the method section. In the first cycle, the percentage score for student observations was 71.8%, while in the second cycle the percentage score for student observations was 88.15%. This improvement is caused by each individual during the learning process using the section method to improve their basketball lay-up technique skills to students.